POSSIBILITIES TO INFLUENCE UPON ORAL FLUID BIOCHEMICAL INDICES IN CHILDREN WITH CHRONIC CATARRHAL GINGIVITIS AND UNDERLYING INSULIN DEPENDENT DIABETES MELLITUS - L. F. Kaskova; V.А. Honcharenko (Український стоматологічний альманах, 2022)
Оbjective of the study was to examine the effect of the suggested therapeutic-preventive complex including oral administration of the complex drug “Kvertulin”, the drops “Imupret, the polyvitaminic complex “Pikovit”, and topical irrigation of the oral cavity with the tooth wash “Exodent” on the biochemical indices of the oral fluid in children with chronic catarrhal gingivitis and diabetes mellitus. Therapeutic and prophylactic measures were performed in children with chronic catarrhal gingivitis, who were prescribed a common complex (groups 1, 2) and proposed by us (group 3), which includes drugs that have antioxidant effects. Determined: protein content by the Lowry method; assessment of POM; the content of HS-groups; activity of glucose-6-phosphate dehydrogenase (PDG); ceruloplasmin. Тhe therapeutic-preventive measures initiated have produced a positive effect on the oral cavity homeostasis and enabled to improve the indices of the study and maintain them on an appropriate level during 6 months. The most significant decrease in the total protein of the oral fluid was observed in the group of patients who were prescribed the complex proposed by us. he OMB study shows that the best results after the end of treatment were obtained in children who were prescribed a complex containing components with antioxidants. Examination of the index of HS-group activity in the oral fluid found its increase after the complex with antioxidants used. It 1.8 times increased in comparison with that one before the treatment. The most substantial changes in the activity of ceruloplasmin was found in 3 group of the study during the whole period of observation. Considerable results after the treatment initiated were found in children from 3 group who were treated according to the therapeutic-preventive complex suggested. G-6-PDG activity decreased in the course of time in all the groups of observation and till the end of the 6th month it was the highest in the 3rd group.